Scholarship of Teaching and Learning und disziplinäre Forschung: Eine komplexe Beziehung

Visualization Task Taxonomy to Understand the Fuzzing Internals - Kummita, Sriteja; Miao, Miao; Bodden, Eric; Wei, Shiyi (ACM Transactions on Software Engineering and Methodology)
Greybox fuzzing is used extensively in research and practice. There are umpteen publications that improve greybox fuzzing. However, to what extent do these improvements affect the internal components or internals of a given fuzzer is not yet understood as the improvements are mostly evaluated using code coverage and bug finding capability. Such an evaluation is insufficient to understand the effect of improvements on the fuzzer internals. Some of the literature visualizes the outcomes of fuzzing to enhance the understanding. However, they only focus on high-level information and no previous research on visualization has been dedicated to understanding fuzzing internals. To close this gap, we propose the first step towards development of a fuzzing-specific visualization framework: a taxonomy of visualization analysis tasks that fuzzing experts desire to help them understand the fuzzing internals. Our approach involves conducting interviews with fuzzing experts and using qualitative data analysis to systematically extract the task taxonomy from the interview data. We also evaluate the support of existing fuzzing visualization tools through the lens of our taxonomy. In our study, we have conducted 33 interviews with fuzzing practitioners and extracted a taxonomy of 120 visualization analysis tasks. Our evaluation shows that the existing fuzzing visualization tools only provide aids to support 10 of them.

Toward Design Principles to Enhance Visual Inquiry Tools for Ecosystem Design - Vorbohle, Christian (Proceedings of the Business Model Conference 2025)

Mode – Kleidung – Textil. Grundlegung und Methode - Kraft, Kerstin; Haase, Birgit

Setting the stage for a flourishing cultural data ecosystem: A spotlight on business models of cultural event platforms - Althaus, Maike; Vorbohle, Christian; Müller, Michelle; Kundisch, Dennis (Electronic Markets)
Abstract Data ecosystems can generate valuable business opportunities, but research on their emergence within specific industries is limited. The cultural event industry is characterized by a multifaceted cultural landscape and a fragmented and heterogeneous market of cultural event platforms. The emerging German cultural data ecosystem, envisioned to share event data in a data space, could foster data-driven innovation and enhance value creation in the cultural event industry. Yet, following the ecosystem-as-structure view, the platforms’ willingness to participate in the cultural data ecosystem depends on whether their business model aligns with at least one of the focal value propositions of the cultural data ecosystem. In this paper, we develop a taxonomy of cultural event platform business models, and derive six archetypes. Additionally, we interview industry representatives of these archetypes to shed light on the benefits and obstacles when participating in the cultural data ecosystem, and to identify potential focal value propositions, corresponding actor roles, and activities. Our work contributes to the discussion on taxonomies of data-sharing business models and the emergence of data ecosystems in the cultural event industry.

The effect of phosphine on hydrogen/ammonia combustion in a plug flow reactor - Dewerth, Mats-Ole

Is Phenylnitrene a Missing Link in the Formation of Polycyclic Aromatic Nitrogen Heterocycles? - Arns, Rahel; McClish, Rory; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy; Kasper, Tina; Schleier, Domenik (Angewandte Chemie International Edition)
Abstract The incorporation of heteroatoms into the framework of polycyclic aromatic hydrocarbons (PAHs), in particular of nitrogen to yield polycyclic aromatic nitrogen heterocycles (PANHs), has been proposed for both astronomical and combustion environments, but no suitable precursors and pathways have been found. Analogous pathways to PAH formation are kinetically or energetically inhibited in the presence of a nitrogen heteroatom. We report on the reaction of phenylnitrene ( 3 PhN, c ‐C 6 H 5 N) with resonance‐stabilized propargyl radicals (C 3 H 3 ) and find that the association reaction bifurcates depending on the orientation of the attacking propargyl radical and yields multiple isomeric products. Among them, we identify the condensed‐ring quinoline and conclude that nitrenes are viable candidates to drive the formation of PANHs.

Is Phenylnitrene a Missing Link in the Formation of Polycyclic Aromatic Nitrogen Heterocycles? - Arns, Rahel; McClish, Rory; Hemberger, Patrick; Bodi, Andras; Bouwman, Jordy; Kasper, Tina; Schleier, Domenik (Angewandte Chemie International Edition)
Abstract The incorporation of heteroatoms into the framework of polycyclic aromatic hydrocarbons (PAHs), in particular of nitrogen to yield polycyclic aromatic nitrogen heterocycles (PANHs), has been proposed for both astronomical and combustion environments, but no suitable precursors and pathways have been found. Analogous pathways to PAH formation are kinetically or energetically inhibited in the presence of a nitrogen heteroatom. We report on the reaction of phenylnitrene ( 3 PhN, c ‐C 6 H 5 N) with resonance‐stabilized propargyl radicals (C 3 H 3 ) and find that the association reaction bifurcates depending on the orientation of the attacking propargyl radical and yields multiple isomeric products. Among them, we identify the condensed‐ring quinoline and conclude that nitrenes are viable candidates to drive the formation of PANHs.

Die Übersetzung von Inspiration in Songs. Referenzielle Songwriting-Praktiken in Bedroom-Studios - Neuhausen, Timo (Popular Music Songwriting as Cultural, Creative, and Economic Practice / Songwriting von populärer Musik als kulturelle, kreative und ökonomische Praxis)

Becoming a One-Person-Band. Zur soziomateriellen Konstitution informeller Bildungspraxis als zirkulierendes Referenzieren - Godau, Marc; Neuhausen, Timo (Rollen und Funktionen von Musik in der digitalen Ära)

Gemeinschaftliches (musik-)kulturelles Handeln. Einführende Gedanken und Beispiele - Ricke, Anna; Bagge, Maren; Fornoff-Petrowski, Christine ((Wahl-)Verwandtschaften. Gemeinschaftliches kulturelles Handeln)

Videospiele(n) im Pädagogikunterricht - Fachdidaktische Überlegungen zum Einsatz eines Videospiels mit historischem Inhalt - Engemann, Mario; Meier, Jette; Rogge, Louisa (Zeitschrift PädagogikUNTERRICHT)

Microscopic origin of gray tracks in KTiOPO4 - Bocchini, Adriana; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)

Guardians of Giving – An Empirical Analysis of the Relationship between Charitable Crowdfunding and Acquisitive Crime,” Proceedings of the 33rd European Conference on Information Systems (ECIS) - Müller, Michelle (Proceedings of the 33rd European Conference on Information Systems (ECIS))

(Wahl-)Verwandtschaften. Gemeinschaftliches kulturelles Handeln

Don't Touch the Power Line - A Proof-of-Concept for Aligned LLM-Based Assistance Systems to Support the Maintenance in the Electricity Distribution System - Kaltenpoth, Sascha; Müller, Oliver (ACM SIGEnergy Energy Informatics Review)
As a possible solution to the demographic change and the resulting knowledge loss due to retirements in the Energy sector, this study aimed to develop a generic pipeline to implement and evaluate proof-of-concepts (PoCs) for LLM-based assistance systems in new domains. Our pipeline contains an LLM-based data generation strategy based on documents, a retrieval-augmented generation (RAG) architecture utilizing prompting techniques on existing German LLMs, and an LLM-based automatic evaluation strategy. We leverage our pipeline to evaluate five LLMs using data from a German DSO. We found that the Llama3 and the Mistral model are appropriately aligned for the task. We plan to pilot the RAG architecture in the DSO's infrastructure for future research and continuously research improvements using the generated human demonstrations.

Music Encoding Conference 2025 - Book of Abstracts
The Music Encoding Conference is the annual meeting of the Music Encoding Initiative (MEI) community and all who are interested in the digital representation of music. Music encoding is a critical component for fields and areas of study including computational or digital musicology, digital editions, symbolic music information retrieval, and digital libraries. This event brings together enthusiasts from various music research communities, including technologists, librarians, music scholars, and students and provides an opportunity for learning and engaging with and from each other.

Komische Fluchten aus der „Deutschen Chronik“ oder (Selbst-)Archivierung der 1980er Jahre? - Elit, Stefan

Exploring Electronic States and Ultrafast Electron Dynamics in AlInP Window Layers: The Role of Surface Reconstruction - Zare Pour, Mohammad Amin; Shekarabi, Sahar; Ruiz Alvarado, Isaac Azahel; Diederich, Jonathan; Gao, Yuyings; Paszuk, Agnieszka; Moritz, Dominik C.; Jaegermann, Wolfram; Friedrich, Dennis; van de Krol, Roel; Schmidt, Wolf Gero; Hannappel, Thomas (Advanced Functional Materials)
Abstract AlInP (001) is widely utilized as a window layer in optoelectronic devices, including world‐record III‐V multi‐junction solar cells and photoelectrochemical (PEC) cells. The chemical and electronic properties of AlInP (001) depend on its surface reconstruction, which impacts its interaction with electrolytes in PEC applications and passivation layers. This study investigates AlInP (001) surface reconstructions using density functional theory and experimental methods. Phosphorus‐rich (P‐rich) and indium‐rich (In‐rich) AlInP surfaces are prepared with in situ monitoring of the process by reflection anisotropy (RA) spectroscopy and confirmed by low‐energy electron diffraction and photoemission spectroscopy. The experimental RA spectra closely match the theoretical predictions obtained by solving the Bethe–Salpeter equation. It is shown that missing hydrogen on P‐rich surfaces and formation of In–In 1D atomic chains on In‐rich surfaces introduce mid‐gap surface states that pin the Fermi level and induce band bending. Time‐resolved two‐photon photoemission measurements reveal ultrafast near‐surface electron dynamics for both P‐rich and In‐rich surfaces, demonstrating photoexcited electrons reaching the surface conduction band minimum and relaxing to mid‐gap surface states on about hundreds of fs. This work provides the most extensive AlInP surface analysis to date, allowing for more targeted surface and interface engineering, which is crucial for the optimization and design of III‐V heterostructures.

Self-assembly of isolated plasmonic dimers with sub-5 nm gaps on a metallic mirror - Devaraj, Vasanthan; Ruiz Alvarado, Isaac Azahel; Lee, Jong-Min; Oh, Jin-Woo; Gerstmann, Uwe; Schmidt, Wolf Gero; Zentgraf, Thomas (Nanoscale Horizons)
We present a cost-effective self-assembly method to fabricate low-density dimer NPs in an NPoM architecture, using the M13 phage as a spacer layer. This will enable the development of dynamic plasmonic devices and advanced sensing applications.